2020
DOI: 10.3390/app10020573
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Microbiome—Study on the Relation and Contiguity between Dogs and Humans

Abstract: Behavioral studies demonstrate that not only humans, but all other animals including dogs, can suffer from depression. A quantitative molecular evaluation of fatty acids in human and animal platelets has already evidenced similarities between people suffering from depression and German Shepherds, suggesting that domestication has led dogs to be similar to humans. In order to verify whether humans and dogs suffering from similar pathologies also share similar microorganisms at the intestinal level, in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…In their article, Mondo et al [4] report the results of a study analyzing the gut microbiota of the German Shepherd dog breed and humans. They found that the German Shepherd's gut microbiota has a different composition than other dog breeds and, in particular, shows a significant resemblance to that of depressed humans.…”
mentioning
confidence: 99%
“…In their article, Mondo et al [4] report the results of a study analyzing the gut microbiota of the German Shepherd dog breed and humans. They found that the German Shepherd's gut microbiota has a different composition than other dog breeds and, in particular, shows a significant resemblance to that of depressed humans.…”
mentioning
confidence: 99%